Aluminum Dimer Containing Bulky 1,2,3-Triazolate Ligand - Issam Kobrsi (Journal of Chemistry)
The first molecular aluminum 1,2,3-triazolato complex was synthesized bearing a bulky 1,2,3-triazolate ligand. Oligomers and polymers were avoided due to the bulkiness and noncoordinating nature of the substituents. The novel Al2N4 ring formed contains symmetrical Al-N bond distances unexpectedly having asymmetric Al-N-N angles of 144.55(15)° and 115.83(14)°. This asymmetry demonstrates the effect of the steric hindrance of the ligand.